Widespread pain and depression are key modifiable risk factors associated with reduced social participation in older adults: A prospective cohort study in primary care. Issue 31 (August 2016) - Wilkie, Ross; Blagojevic-Bucknall, Milisa; Belcher, John; Chew-Graham, Carolyn; Lacey, Rosie J.; McBeth, John
Abstract : Abstract: In older adults, reduced social participation increases the risk of poor health-related quality of life, increased levels of inflammatory markers and cardiovascular disease, and increased mortality. Older adults frequently present to primary care, which offers the potential to deliver interventions at the point of care to increase social participation. The aim of this prospective study was to identify the key modifiable exposures that were associated with reduced social participation in a primary care population of older adults. The study was a population-based prospective cohort study. Participants (n = 1991) were those aged ≥65 years who had completed questionnaires at baseline, and 3 and 6-year follow-ups. Generalized linear mixed modeling framework was used to test for associations between exposures and decreasing social participation over 6 years. At baseline, 44% of participants reported reduced social participation, increasing to 49% and 55% at 3 and 6-year follow-up. Widespread pain and depression had the strongest independent association with reduced social participation over the 6-year follow-up period. The prevalence of reduced social participation for those with widespread pain was 106% (adjusted incidence rate ratio 2.06, 95% confidence interval 1.72, 2.46), higher than for those with no pain. Those with depression had an increased prevalence of 82% (adjusted incidence rate ratio 1.82, 95% confidence interval 1.62, 2.06). These associations persisted in multivariate analysis. Population ageing will be accompanied by increasing numbers of older adults with pain and depression. Future trials should assess whether screening for widespread pain and depression, and targeting appropriate treatment in primary care, increase social participation in older people.